Unjuk kerja mesin menggunakan bahan bakar arak Bali berkonsentrasi 90% - Sukadana, I Gusti Ketut; Bandem Adnyana, I Wayan; Dwijana, I Gusti Komang (Jurnal Energi Dan Manufaktur; Vol 14 No 2 (2021), 2022)
Arak Bali which is produced from the distillation process and palm or coconut juice or palm sugar can produce bioethanol with a concentration greater than 90%, not suitable to drink but suitable to be used as fuel. Arak Bali has an octane value of 108.6 and premium fuel has an octane value of 88, so the arak Bali is suitable to be used as alternative fuel. Performance testing was performed using a four-cylinder 125 cc motor vehicle with a compression ratio of 9: 1 using fuels arak Bali compared to premium. Testing is done with engine rotation variation from 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, 5000 rpm for performance: torque, power, fuel consumption, specific fuel consumption and exhaust emissions include: hydrocarbon, carbon monoxide, oxigene and carbon dioxide. Testing results the performance of the machine using fuel arak Bali produces the highest torque of 7.15 Nm, the highest power of 5.606 Kw, fuel consumption of 0.161 grams / sec at engine speed 3000 rpm. Specific fuel consumption is 0.1172 kg / kWh at engine speed 5000 rpm. Exhaust emissions generated in the form of hydrocarbon, carbon monoxide, oxigene and carbon dioxide, to indicate that the arak Bali can be used as alternative fuel.